2001
DOI: 10.1097/00001756-200108080-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ensheathing cells transplanted into photochemically damaged spinal cord

Abstract: Transplantation of olfactory ensheathing cells (OECs) into photochemically damaged rat spinal cord diminished astrocyte reactivity and parenchyma cavitation. The photochemical lesion performed at T12--L1 resulted in severe damage to the spinal cord, so that during the first 15 days postoperation all rats dragged their hindlimbs and did not respond to pinprick. The maximal area and volume of the cystic cavities were lower in transplanted than in non-transplanted rats, not significantly at the T12--L1 lesion sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
7

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 27 publications
3
55
0
7
Order By: Relevance
“…Secondly, OECs transplanted in lesioned spinal cords induce a downregulation of GFAP and proteoglycan expression by the reactive astrocytes (Verdú et al, 2001). In the present study, we confirm these results at a longer time, 3 months postlesion, when the injury process has reached a steady state.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Secondly, OECs transplanted in lesioned spinal cords induce a downregulation of GFAP and proteoglycan expression by the reactive astrocytes (Verdú et al, 2001). In the present study, we confirm these results at a longer time, 3 months postlesion, when the injury process has reached a steady state.…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies, we reported that during the first 60 min posttrauma, light and electron microscopy showed an important cytotoxic edema with astrocytic swelling, hemorrhagic extravasation, and myelin degradation in the lesion site. After 15 days, a cavity was observed in the necrotic area, and hypertrophied, heavily GFAP-and proteoglycan-stained astrocytes were seen delimiting this cavity (Verdú et al, 2001. A photochemical lesion in adult rats can induce graded severity of spinal cord injury.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent data suggest that the mechanism of functional return may be more complex than regrowth of lesioned axons. In fact, OEC transplantation protects spinal tissue from secondary damage and prevents cavitation, [241][242][243][244][245][246] enhances vascularization of the lesion site 235,246 and promotes branching of neighboring axons spared by the primary injury, 247 all of which might subserve improved functional outcome. While earlier transplant experiments sought to isolate OECs without other cellular components of the olfactory nerve, recent work suggests that the recovery of function is enhanced by including other cell types, such as olfactory nerve fibroblasts (ONFs), in the graft.…”
Section: In the Spotlight: Schwann Cells And Oecsmentioning
confidence: 99%